ANALISIS KESULITAN MEMBACA PERMULAAN PADA SISWA KELAS II DI SEKOLAH DASAR - Octavia, Reineta Dwi; Nugraha, Fajar; Nurani, Riga Zahara (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2023)
Reading is one aspect of language skills that students must have. Reading at the beginning level is an activity to learn to recognize written language and students are required to voice the symbols of language sounds. The purpose of this study was to analyze the form of difficulty and factors causing the difficulty of learning to read grade 2 elementary school students in Tasikmalaya Regency. The research method used is qualitative descriptive, data collection is carried out through student reading tests which are confirmed by observation and interview process. The sample in this study was 2 male students and 1 female student who had been given a reading test. The results of this study state that the form of difficulty and the factors causing the difficulty of learning to read each student are different. Based on the test results that students followed, the forms of reading learning difficulties experienced were: difficulty recognizing letters, distinguishing similar letter shapes, combining letters into words, and wrong pronunciation by replacing letters. The factors causing students' difficulty learning to read are divided into two factors, namely internal factors.